1999
DOI: 10.1016/s0370-2693(99)00584-5
|View full text |Cite
|
Sign up to set email alerts
|

Experimental verification of neutron phenomenology in lead and transmutation by adiabatic resonance crossing in accelerator driven systems

Abstract: Energy and space distributions of spallation neutrons (from 2.5 and 3.57 GeV/c CERN proton beams)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 7 publications
(3 reference statements)
0
11
0
Order By: Relevance
“…118). At about 46 cm from the centre of the lead volume (hole 10, z = +7.5 cm) the capture rate is 14 900 per 10 9 protons on our 7. For instance sodium iodide (NaI).…”
Section: Selected Examples Of Procedures For An Activatormentioning
confidence: 83%
See 3 more Smart Citations
“…118). At about 46 cm from the centre of the lead volume (hole 10, z = +7.5 cm) the capture rate is 14 900 per 10 9 protons on our 7. For instance sodium iodide (NaI).…”
Section: Selected Examples Of Procedures For An Activatormentioning
confidence: 83%
“…One can observe a very hard spectrum, which is required for instance in order to fission the TRUs. The subsequent five spectra (6)(7)(8)(9)(10) correspond to different vertically segmented levels in the lead surrounding the core, in steps of 40 cm. All spectra are average spectra over the vertical bin.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Accelerator Driven System (ADS), which consist in the coupling of an accelerator to a target installed in the center of a nuclear reactor, are viewed today as one of the possible ways to reduce the nuclear waste volume and the long term toxicity. It has been experimentaly demonstrated that an ADS has the potential to produce energy [1] but also to destroy nuclear waste [2]. It can also be used for radioactive isotope production, for example for medical applications [3].…”
mentioning
confidence: 99%